EKSISTENSI PARALEGAL SEBAGAI PEMBERI BANTUAN HUKUM DI PROVINSI MALUKU - J. Mustamu; H. Salmon (UNES Law Review, 2021)
Law Number 16 of 2011 concerning Legal Aid mentions Paralegals as one of the Legal Aid Providers. Technically, the role of the new Paralegal is regulated in the Minister of Law and Human Rights Regulation Number 1 of 2018 concerning Paralegals. This study aims to examine the existence of paralegals in providing legal aid to the poor in one of the provinces in Indonesia, namely Maluku Province. The results of this study found Paralegal activities in Maluku Province, especially Ambon City, the obstacles for Paralegals in carrying out their roles and the solutions offered to overcome these obstacles.